Science communication in action: lessons from a mixed-methods case study of a large science festival - King, Katherine; Kessler, Talia; Nimox, Kari; Alemdar, Meltem (Frontiers in Communication, 2025)
IntroductionScience festivals are a mechanism for connecting public audiences with science topics. Scholars have identified best practices for science communication (Peterman and Young, 2015), facilitating research on how and to what extent effective science communication occurs in the context of science festivals.MethodsThis mixed-methods evaluation case study centers the experiences of exhibitors (i.e., science communicators) at a large science festival event. We use a convergent parallel mixed methodological approach with an intent to triangulate observation, survey, and group interview data.ResultsObservation data documented the use of effective communication practices by exhibitors, such as clear messaging and engaging activities. Best practices for science communication were documented more frequently by exhibitors from educational institutions and non-profit or other organizations, compared to exhibitors from large corporate sponsors. Exhibitors described positive impacts of participating in the event, which provided valuable professional development, reinforced their communication skills, and fostered a sense of community.DiscussionThe findings of this study have implications for those involved in recruiting and training scientists to participate in outreach events. Future festivals should continue to prioritize hands-on, interactive methods, while offering support for science communication best practices, particularly for volunteers who are less practiced in communicating science, such as those outside academia. In addition, this work highlights the value of robust evaluation and research to understand the impacts of science festivals, not just on attendees, but on those tasked with communicating science.